The Impact of Green Operational Practices, Digital HR Innovation, and Work Process Discipline on Employee Performance in an FMCG Company - Gustsany Rangga Wijaya Sutarto; Imron Rosidi NH; Abdul Rauf (Eastasouth Institute, 2026)
This study examines the impact of green operational practices, digital human resource (HR) innovation, and work process discipline on employee performance at PT Savoria Kreasi Rasa. The population consisted of production employees, and purposive sampling was used to select respondents based on specific criteria, resulting in 63 samples. Primary data were collected through questionnaires using a Likert scale. Data were analyzed using multiple linear regression to test both partial and simultaneous effects of the independent variables on employee performance. Employee performance was measured through work quality, quantity, timeliness, compliance, and responsibility in completing tasks. The results show that green operational practices do not have a significant effect on employee performance, digital HR innovation has a negative and significant effect, and work process discipline has a positive and significant effect. Simultaneously, the three independent variables significantly affect employee performance. These findings indicate that environmentally oriented operational practices and digital HR systems do not automatically improve individual performance unless they are integrated with employee readiness and daily work activities. In contrast, consistent work process discipline plays a dominant role in improving employee performance in a manufacturing setting. This study contributes to human resource management literature by emphasizing the importance of aligning sustainability-oriented operations, HR digitalization, and disciplined work behavior to improve employee productivity. The findings also provide practical implications for companies seeking to optimize internal systems and strengthen employee performance outcomes.